A study on the development of livable city centres: The case of Famagusta, North Cyprus - Rafiemanzelat, Reihaneh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
The concern about the livability in urban spaces has led to an increasing interest in findings from analyses aiming to quantify livability in particular places such as city centres. As city centres have always been known by their functions, activities and social interactions in traditional cities, today with the effect of fast urbanization and uncontrolled growth of cities toward outwards of cities, also changing types of life style, we lose the meaning and use of the concept of city centre in many cases. In addition, many cities become too dependent on the industry sector, and therefore city centres are left without adequate diversity, which led to the loss of the livability of city centres. This study aims to focus on the characteristics of city centres and the main factors to achieve parameters of livability of the city centre and propose a strategy to achieve a livable city centre in case of Famagusta, North Cyprus. The thesis first presents a brief summary of the research methodology, second, reviews the literature in order to provide a theoretical background for understanding the concept of livable city centres, third, reviews the evolution of city centres, fourth, reviews livable city centre examples from the world, and finally, presents and interprets the results of the user survey carried out by the candidate within the city of Famagusta, in order to provide a clear understanding of people's views about their city and its centre . The study contributes some experiential evidence to investigate the claim benefits and deficiencies in terms of effects of physical, social and economic parameter on the overall perception of livability of the residents in central areas. The research methodology includes literature review, data collection from both qualitative and quantitative analysis, user survey and observations. Keywords: City centre, Livable city centre, User survey, Famagusta

ÖZ: Kent alanlarının yaşanabilirliği ile ilgili endişeler, kent merkezi gibi kent alanlarının yaşanabilirliği ile ilgili araştırma sonuçlarına ve analizlerine olan ilginin artmasına neden olmuştur. Geleneksel kentlerde işlevleri, etkinlikleri ve sosyal etkileşimleri ile odak noktası olan kent merkezleri, hızlı kentleşme, denetimsiz büyüme ve yaşam tarzındaki değişimler nedeniyle, moden kentlerde anlamını ve işlevini gittikçe yitirmektedir. Bunun ötesinde, birçok kentin endüstri sektörüne bağımlı hale gelmesi ve kent merkezlerinin yeterli çeşitliliğe sahip olmaması nedeniyle kentten kentten uzaklaşılmakta ve yaşanabilik azalmaktadır. Bu çalışma, kent merkezi kavramına, özelliklerine ve kent merkezlerinde yaşanabilirliği sağlamak için gerekli temel etkenlere yoğunlaşmakta, ve Gazimağusa kentinin (Kuzey Kıbrıs) kent merkezinde yaşanabilirliği artırmak için bir strateji geliştirmeyi amaçlamaktadır. Bu çalışma, ilk olarak kullanılan araştırma yöntemini tanıtır, ikinci olarak yaşanabilir kent merkezlerinin kavramını anlamak için bir teorik altyapı sağlamak üzere literatürü gözden geçirir, üçüncü olarak kent merkezlerinin tarih içindeki evrimini açıklar, dördüncü olarak dünyadan yaşanabilir kent merkezi örneklerini değerlendirir, ve son olarak, adayın Gazimağusa’da ikamet eden kullanıcılarla yaptığı anket sonuçlarını sunar ve yorumlar. Bu kullanıcı araştırmasıyla, Gazimağusa’da ikamet eden kişilerin, kent merkezi ve genel kent özellikleri ile ilgili görüşleri saptanmış olup, merkezi alanlarda yaşayanların, fiziki, sosyal ve ekonomik bakımdan eksiklikler ve faydalarla birlikte yaşanabilirlikle ilgili algılarına yönelik bazı deneysel kanıtları ortaya konmaktadır. Araştırma yöntemi, literatür taraması, nicel ve nitel analiz yoluyla veri toplanması, kullanıcı anketi ve gözlem tekniklerini içermektedir. Anahtar Kelimeler: Kent merkezi, Yaşanabilir kent merkezi, Kullanıcı Anketi, Gazimağusa.
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2014. Supervisor: Prof. Dr. Derya Oktay.
Keywords: Architecture; Urban Design; Community development, Urban; Regional development--Sustainable urban development; City Centre; Livable City Centre; User Survey; Famagusta